Інструмент з алмазного і абразивного волокна для фінішної обробки неметалевих матеріалів - Філатов, Ю.Д.; Крамар, В.Г.; Сідорко, В.І.; Ковальов, С.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
Experienced technology of the fabrication diamond-abrasive fiber to production working element of the tool is described. The results of the estimation to capacity of the processing and quality of the processed surfaces product from non-metallic materials are presented.